DESAIN AGROFORESTRY PADA LAHAN KRITIS (STUDI KASUS DI KECAMATAN INDRAPURI KABUPATEN ACEH BESAR) - . Bukhari; Indra Gumay Febryano (PERENNIAL, 2010)
Design of agroforestry has the objectives of improving the system which has been existing and providing directives for agribusiness on the basis of physical, economical, and socio-cultural condition. Design of a system is inevitably related with pre-diagnosis and diagnosis activities which are aimed at discovering the existing constraints and problems inside the system, followed by technological intervention for system improvement and determining the best agroforestry system in critical land condition. Method used in this study was identifying the existing agroforestry system, followed by evaluation of land suitability, financial analysis and community social analysis. This study found three agroforestry systems based on the existing components, namely agrisilviculture, silvopasture, and agrisilvopasture. Evaluation of land suitability showed that in general, land suitability ratings for woody crops and perennial crops were categorized as moderately suitable (S2), while those for annual crops / non rice food crops were categorized as marginally suitable (S3). Results of financial analysis showed that all existing agroforestry system are feasible to be practiced, with highest benefit cost ratio 2.7 was found in agrisilvopasture system. On the basis of landscape consideration, species of Non-MPTs were more adapted if they were planted in hill ridge, while that of species of MPTs and perennial crops in slope and valley, and that of annual crops in valley. Key words: agroforestry, land suitability, critical land, design